Systems pharmacology dissection of the anti-stroke mechanism for the Chinese traditional medicine Xing-Nao-Jing - Yuhua Chen; Yue Sun; Wende Li; Hong Wei; Tianlin Long; Hua Li; Quanhua Xu; Wei Liu (Elsevier, 2018)
Xing-Nao-Jing (XNJ) is a well-known injection that has been extensively applied in clinical treatment of stroke in China. However, the underlying mechanism of clinical administration of XNJ in stroke remains unclear. In this study, a systems pharmacology strategy based on pharmacokinetic and pharmacodynamics data was applied to analyze the pharmacological effect of XNJ on stroke. Sixteen active compounds were filtered from XNJ through Drug-likeness (DL) and Brain-blood-barrier (BBB) evaluations. Ninety-four potential targets of these active components were identified by SysDT and SEA. Biological process and pathway enrichment analyses of these targets demonstrated that XNJ exerted anti-stroke effects by biological processes and pathways, such as the response to oxidative stress, regulation of blood pressure, calcium signaling pathway, and apoptosis. Integrating the compound-target network and stroke-related PPI network, we found that Akt1, HIF-1α and ITGB2 may play key roles in the treatment of stroke. The experiments demonstrated that oxycurcumenol may prevent PC12 cells from oxidative stress-induced cell damage. Our study indicates that XNJ has an effect on stroke by protecting neuro cells from oxidative stress-induced cell damage via HIF1α, and the research strategy at the systems pharmacology level is feasible to reveal the mechanisms of novel lead compounds from natural products.